Studi Evaluatif dan Analisis Urgensi Harmonisasi Kebijakan Manajemen Risiko Sektor Publik di Indonesia - Akhmad Nur Imtihanul Hikam; Bagus Dwi Septian; Luthfia Almas; M. Rafli Al Mubarok; Muhammad Jusuf; Syifa Auliya Mahendra (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
Effective risk management is essential for good governance in the public sector, supporting efficiency, transparency, and accountability. Although SNI ISO 31000:2018 has been established as the national standard, its application in government institutions remains inconsistent. This study examines the alignment of risk management policies with SNI ISO 31000:2018, evaluates its relevance as a policy reference, and explores the urgency of harmonization. A qualitative approach was used through document analysis and semi-structured interviews with academics and practitioners. Content analysis employed an evaluation matrix based on principles, framework, and processes of risk management, while interview data were analyzed thematically. Results indicate significant variation in adoption, with conformity ranging from 0% to 87.23%. Instead of enforcing detailed harmonization, the study highlights the need to build shared perceptions and understanding of risk management to enhance cross-sector collaboration within the National Development Risk Management framework.